An evaluation of hospitality industry's efficiency using data envelopment analysis (DEA) - Hafizah Dalilah, Mohamad Zin (2015)
This survey was conducted to identify the efficiency variable’s influencing hospitality industry by using Data Envelopment Analysis and to evaluate of efficiency of hotel using Data Envelopment Analysis. The sample is constituted by 9 of five star hotel (Grand Hyatt Hotel, Traders Hotel, Berjaya TS Hotel, Shangri-La Hotel, JW Marriott Hotel, Sama Sama Hotel, Hilton PJ Hotel, Majestic Hotel, and Royale Chulan Hotel) that operating in Malaysia. The efficiency for the selected hotels is estimated through the data envelopment analysis methodology. The efficiency ranking can be explained by interaction between variables. Then, the hotel inefficiency mainly causes of the input and output configuration. A direction for future research can be easy to make of input and output. Furthermore, the inefficiency causes was identify and suggestion for the manager or hotel owners are made to increase hotel efficiency. This is one of the a few research of study measuring hotel efficiency in Malaysia. Moreover, it identify the inefficiency causes of hotel and offer suggestion to fixing the lacks that be found in hotel management.